Prevalence of Development of Eating Disorders among Students in University of Cyberjaya - Raziq Irfan Azman; Balqis Fatini Mohamad Nasser; Izleen Suhanis Izlan; Farah Nadhirah Muhammad Najib; Mohammad Husni Hj. Ahmad Jamal (Asian Journal of Medicine & Health Sciences, 2022)
Introduction: The World Health Organization (WHO) estimates that worldwide, 70 million people have an eating disorder. The aim of this research is to determine the prevalence of development of eating disorders and the association between selected socio-demography and development of eating disorders among the students of University of Cyberjaya.  Methods: A descriptive cross-sectional study was conducted among students in University of Cyberjaya, Malaysia. A total of 231 students were selected via stratified random sampling and simple random sampling. A self-administered questionnaire was adapted from the validated Eating Attitude Test-26 (EAT-26). The questionnaire administered was a combination of the Eating Attitude Test-26 and items related to socio-demographic profile. Descriptive analyses were performed to provide background information of at-risk students by selected socio-demographic profile.  Results: 38.1% were found to be at risk of developing eating disorders with a higher prevalence among females (39.4%) compared to males (34.4%). There was no significant association seen in the selected socio-demographic (gender, age, ethnicity, faculty of study and residency) except for monthly allowance (p-value = 0.014).  Conclusion: The prevalence of developing eating disorders is high among students in University of Cyberjaya with the majority among females. Strategies to detect eating disorders should be implemented, enabling them to seek help from health professionals as early as possible.